Efficacy of autologous serum therapy in ASST positive and ASST negative patients in chronic urticaria in a tertiary care centre - Raghavendra KR; Bangaru H (PAGEPress Publications, 2022)
Background: Autologous Serum Therapy (AST) has been a recent therapeutic choice for a variety of chronic diseases such as allergic, inflammatory, infectious, and autoimmune disorders, however evidence were not convincing the beneficial effects of autologous serum therapy in treatment of Chronic urticaria. Chronic Urticaria (CU) is common dermatological condition and very disturbing to the patient as well as physician. A new observation was made about the abnormal type 1 reactions to intradermal autologous serum injections in some CU patients. This has led to the new subgroup of "autoimmune chronic urticaria". The autologous serum skin test (ASST) it is an intradermal test result in immediate hypersensitivity-type skin reactions in a subpopulation of CU patients and giving promising evidence of therapeutic and diagnostic benefit. Already autologous whole blood (AWB) injection has been used as one of old treatment modalities for chronic urticaria. Objectives: To study the efficacy of autologous serum therapy in patients with chronic urticaria & compare its results in ASST(+) & ASST(-) chronic urticaria patients. Methodology: Approximately 5ml of patients' blood was drawn in a plain vacutainer and centrifuged at 3000 r.p.m. for 10 min, separated 2.5 ml serum injected deep intramuscularly into gluteus muscle & injections were repeated every week for about 9 weeks & a repeat follow up at 20 weeks was done. Results: Out of total 20 patients excellent improvement seen in 6 patients in terms of decrease in Urticaria assessment severity score whereas ten patients showed partial response and two patients showed no response & two patients lost follow up. Ten patients with ASST (+) & six patients of ASST(-) showed little improvement in urticaria severity score. Conclusion: AST therapy is a cost-effective adjuvant modality for reducing the severity of symptoms of chronic urticaria. In some patients its giving long term remission period and it decreases the updosing of antihistamines.